PENAJAMAN KOMPETENSI SISWA SEKOLAH KEJURUAN DI BIDANG ESTIMASI BIAYA KONSTRUKSI JALAN - Mahardi, Purwo; Susanti, Anita; Supriyatno, Dadang; Widayanti, Ari; Ristriana, Amanda; Wibisono, Endro; Refa Haratama, Kusuma (Jurnal Abdi Masyarakat, 2024)
Vocational school students were introduced to the preparation of cost budget plans in the subject of construction cost estimation, but it was limited to the budget plan of building buildings, while the expertise of estimators was divided into buildings and roads. Therefore, road budget plan training is considered necessary and the D4 Transportation study program carries it out in the form of Community Service (CS). CS was held at SMKN 3 Surabaya with a total of 32 students in grade XII of Building Modeling and Information Design with an emphasis on 3 main materials, namely the definition of RAB, the stages of preparing RAB, and the calculation of the volume of work in RAB. PKM was proven to increase the level of students' understanding of the definition of RAB (22%), the stages of preparing RAB (35%) and the calculation of work volume (19%).